Preparation method of carbon aerogel with high temperature resistance and high mechanical stability
By growing a three-dimensional graphene sheet array on PF aerogel, the problem of insufficient strength and toughness of carbon aerogel is solved, and the preparation of carbon aerogel with high temperature resistance and high mechanical stability is achieved, which improves its thermal insulation performance.
Patent Information
- Application Number
- CN202411386688.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The strength and toughness of existing carbon aerogels are poor, making them difficult to be directly used in thermal insulation materials, and reinforcement bodies such as fibers are often required.
After reacting with the formaldehyde solution with anhydrous sodium carbonate, anhydrous sodium carbonate was added to form a PF aerogel, and a three-dimensional graphene sheet array was grown on it by chemical CVD method to form a high temperature resistance and high mechanical stability. Carbon aerogel.
It improves the strength and toughness of the carbon aerogel, improves its thermal insulation properties, and forms a composite material with higher mechanical stability and specific surface area.
Smart Images

Figure CN119240679A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon aerogel preparation, and in particular relates to a method for preparing a carbon aerogel with high temperature resistance and high mechanical stability. Background Art
[0002] Aerogel is a mesoporous solid material with extremely low bulk density, low thermal conductivity, large specific surface area and high porosity. Aerogel insulation materials are known as "super insulation materials" and have broad application prospects in aerospace, petrochemical, construction, energy, medicine and other fields. The development of nanotechnology has promoted the development of new methods for synthesizing new aerogel materials. Different types of aerogels have different high temperature resistance ranges, so their application scenarios are also different. Aerogel insulation materials can be mainly divided into inorganic oxide aerogels (SiO2, Al2O3, ZrO2, etc.), organic aerogels (phenolic, polyimide, cellulose, etc.), carbon aerogels and carbide aerogels (SiC, SiCO, ZrCO, etc.) according to their composition.
[0003] At present, according to the different raw materials and preparation processes, carbon aerogels are mainly divided into two types. One is to use low-dimensional nanocarbon materials such as graphene and carbon nanotubes to form a three-dimensional network gel through self-assembly. The carbon aerogel obtained by this method generally has ultra-light and ultra-elastic properties, but is rarely used in actual thermal insulation applications. Among them, graphene aerogel is a porous network material formed by overlapping single or few layers of graphene, and the internal pores are filled with air. There are many preparation methods, including chemical vapor deposition, 3D printing, sacrificial template method, hydrothermal method, foaming method, ice crystal template method, microemulsion method, etc. Graphene aerogel has many novel properties, including ultra-low density, excellent mechanical properties, high specific surface area, high conductivity, etc. The other is based on organic aerogel carbonization, including resorcinol-formaldehyde, resorcinol-furfural, phenol-formaldehyde, phenolic resin-hexamethylenetetramine and other systems. Among them, the resorcinol-formaldehyde system is the most commonly used. The pure carbon aerogels currently prepared are brittle and fragile, with poor strength and toughness, making them difficult to be used directly as thermal insulation materials in thermal protection systems. It is often necessary to introduce reinforcements such as fibers into them. Summary of the invention
[0004] In order to solve the shortcomings of existing carbon aerogels, such as poor strength and toughness, the purpose of the present invention is to provide a method for preparing carbon aerogels with high temperature resistance and high mechanical stability, which improves the mechanical properties of traditional carbon aerogels, such as strength and toughness, and enhances their thermal insulation properties.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a carbon aerogel with high temperature resistance and high mechanical stability comprises the following steps: After the ethanol solution containing resorcinol reacts with the formaldehyde solution, anhydrous sodium carbonate is added, and after the reaction, the solution is allowed to stand for aging to obtain a sample; The sample was soaked in ethanol and dried to obtain PF aerogel; A three-dimensional graphene sheet array was grown on PF aerogel using chemical CVD method to obtain a carbon aerogel with high temperature resistance and high mechanical stability.
[0006] A further improvement of the present invention is that the usage ratio of resorcinol, water and ethanol in the ethanol solution containing resorcinol is 12.5g-22.5g:60ml:40ml.
[0007] A further improvement of the present invention is that the usage ratio of resorcinol to formaldehyde solution is 12.5 g to 22.5 g: 15 ml to 27 ml, and the mass concentration of the formaldehyde solution is 37% to 40%.
[0008] A further improvement of the present invention is that the mass of anhydrous sodium carbonate is 1 / 500 to 1 / 2000 of the mass of resorcinol.
[0009] A further improvement of the present invention is that the temperature of static aging is 30-60° C. and the time is 12-36 hours.
[0010] A further improvement of the present invention is that the soaking time is 2-4 days.
[0011] A further improvement of the present invention is that a VG array is grown on a PF aerogel by a chemical CVD method to obtain a carbon aerogel with high temperature resistance and high mechanical stability, comprising the following steps: The PF aerogel was kept at 1000-1300°C for 6-8h under a mixed gas of methane and hydrogen.
[0012] A further improvement of the present invention is that the temperature is raised to 1000-1300°C at a heating rate of 5°C / min in an argon atmosphere, and after being kept warm for 6-8 hours, the temperature is lowered to room temperature at a cooling rate of 10°C / min in an argon atmosphere.
[0013] A further improvement of the present invention is that the flow ratio of methane to hydrogen is 30:160.
[0014] A carbon aerogel with high temperature resistance and high mechanical stability.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention organically combines vertical graphene sheets with phenolic resin, which has the following advantages: In the preparation process of the present invention, the atmospheric pressure drying method is used instead of the supercritical drying method, which reduces the cost and danger of the preparation process; in the present invention, the three-dimensional graphene sheet array (VGSs) manufactured on the PF substrate by the chemical CVD method will not agglomerate, but will be evenly distributed inside and on the surface of the PF aerogel, and it can be independently self-supporting. Therefore, the prepared carbon aerogel PF@VGSs composite material forms a three-dimensional porous structure with better flexibility. Compared with the amorphous carbon in the traditional carbon aerogel, VGSs has better mechanical stability, higher specific surface area and lower density, so introducing it into the PF aerogel can improve the overall strength and toughness of the material.
[0016] Furthermore, the process of growing VGSs by chemical CVD has a great influence on the performance, because the size of VGSs needs to match the PF aerogel. If it is too large or too small, it cannot form a good three-dimensional structure with the PF aerogel and improve the mechanical properties of the whole material. Therefore, during the CVD growth process, the ventilation volume of methane and hydrogen should be controlled to control the growth process of the whole VGSs. In the CVD growth process, the role of methane is the carbon source, and the role of hydrogen is to etch the carbon source deposited on the PF aerogel. Therefore, it is necessary not only to control the ventilation volume of methane and hydrogen separately, but also to control the flow ratio between the two to 30:160, in order to achieve the purpose of synthesizing a PF@VGSs composite material with good performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The microstructure characteristics of PF@VGSs; Figure 2 Bending stress-strain curves of PF and PF@VGSs composites. DETAILED DESCRIPTION
[0018] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0019] The present invention discloses a method for preparing a carbon aerogel with high temperature resistance and high mechanical stability. The method combines the sol-gel method with the chemical CVD method, fully utilizes and combines the advantages of various carbon aerogels, and successfully prepares phenolic resin @ vertical graphene sheets (PF@VGSs) to organically combine two carbon aerogels to form a three-dimensional stable structure. The specific method is as follows, including the following steps: (1) Add 60 ml of water and 40 ml of ethanol into a 250 ml beaker and stir for 30 seconds to obtain a mixed solution; (2) Then, the beaker containing the mixed solution in step (1) was moved into a 30°C water bath to continue stirring the reaction. Then, 12.5 g to 22.5 g of resorcinol was weighed and added to the above solution (12.5 g, 17 g or 22.5 g were added in the experiment) and stirred for 10 min to obtain a mixture. (3) Then, add 15 ml to 27 ml of formaldehyde aqueous solution (mass concentration 37% to 40%) to the mixture in step (2) (in actual experiments, 15 ml, 21 ml or 27 ml were added respectively) and stir to react for 5 min; (4) then adding anhydrous sodium carbonate in an amount of 1 / 500 to 1 / 2000 of the mass of the resorcinol added in step (2) to the solution obtained in step (3) (in actual experiments, 1 / 500, 1 / 1000 or 1 / 2000 were added, respectively) and stirring the mixture for 30 minutes to obtain a mixed solution; (5) adjusting the temperature of the water bath heating device containing the mixed solution in step (4) to 30-60°C and allowing to age for 12-36 hours to obtain an aged sample; (6) After the aged sample in step (5) is placed at room temperature for 1 hour, it is soaked in ethanol for 2-4 days, and the ethanol is replaced once a day until all the water therein is replaced, thereby obtaining a sample after replacement; (7) drying the sample after replacement in step (6) at room temperature for 2 h, and then placing it in a constant temperature forced air drying oven and drying it at 85° C. for 12 h. After drying, taking out the PF aerogel to obtain the PF aerogel; (8) The PF aerogel in step (7) was transferred into a corundum boat, and then placed in a high-temperature tube furnace. After heating to 1000-1300°C at 5°C / min in an argon atmosphere, the argon gas was turned off, and methane (CH4) and hydrogen (H2) were introduced at the same time, wherein the flow rate of CH4 was 30ml / min and the flow rate of H2 was 160ml / min, and the temperature was kept constant at 1000-1300°C for 6-8h. After the constant temperature was completed, the temperature was cooled at a rate of 10°C / min. When the temperature was cooled, the methane and hydrogen were turned off, and the argon gas was turned on. After the high-temperature tube furnace was cooled to room temperature, the argon gas was turned off, and the corundum boat was taken out to obtain a carbon aerogel with high temperature resistance and high mechanical stability, which was recorded as PF@VGSs carbon aerogel.
[0020] The following are specific embodiments.
[0021] Example 1 (1) Add 60 ml of water and 40 ml of ethanol into a 250 ml beaker and stir for 30 seconds; (2) Then, the beaker containing the mixed solution in step (1) was moved into a 30°C water bath and continued to stir and react. Then, 17 g of resorcinol was weighed and added to the above solution and stirred for 10 min. (3) Then, add 21 ml of formaldehyde aqueous solution (37%-40%) to the solution in step (2) and stir to react for 5 minutes; (4) Then, anhydrous sodium carbonate (17 mg) in an amount 1 / 1000 of the mass of resorcinol added to the solution in step (2) was added to the solution in step (3), and the mixture was stirred for reaction for 30 minutes; (5) The mixed solution in step (4) was placed in a water bath and heated to 45°C and aged for 24 hours; (6) After the aged sample in step (5) is placed at room temperature for 1 hour, it is immersed in ethanol for 3 days, and the ethanol is replaced every day until all the water therein is replaced; (7) Dry the sample after replacement in step (6) at room temperature for 2 h, then place it in a constant temperature forced air drying oven and dry it at 85 °C for 12 h. After drying, take out the PF aerogel; (8) The PF aerogel in step (7) was transferred into a corundum boat, and then placed in a high-temperature tube furnace. After heating to 1200°C at 5°C / min in an argon atmosphere, the argon gas was turned off, and methane (CH4) and hydrogen (H2) were introduced at the same time, with a CH4 flow rate of 30ml / min and a H2 flow rate of 160ml / min. The temperature was kept constant at 1200°C for 6h. After the constant temperature was reached, the temperature was cooled at a rate of 10°C / min. When the temperature was cooled, the methane and hydrogen gases were turned off, and the argon gas was turned on. After the high-temperature tube furnace was cooled to room temperature, the argon gas was turned off, and the corundum boat was taken out to obtain the PF@VGSs carbon aerogel.
[0022] from Figure 1 It can be seen that VGSs grow evenly on the surface of the PF matrix, forming a three-dimensional structure.
[0023] from Figure 2 It can be seen that the bending strength of the two carbon aerogel composite samples is very different. At lower strains, both samples showed linear elastic deformation, but as the stress continued to increase, after undergoing elastic deformation, both samples showed obvious plastic deformation. As the strain increased, the stress did not suddenly decrease, but tended to stabilize within a certain range. However, compared with PF carbon gel, the stress of PF@VGSs carbon gel sample at the yield point has been greatly improved. Although plastic deformation also occurred after elastic deformation, the strain range of plastic deformation was smaller. This shows that the introduction of VGSs in the material greatly improved the brittleness of PF and increased its maximum stress that it can withstand. Compared with PF materials, PF@VGSs composite materials have better mechanical stability.
[0024] Example 2 (1) Add 60 ml of water and 40 ml of ethanol into a 250 ml beaker and stir for 30 seconds; (2) Then, the beaker containing the mixed solution in step (1) was moved into a 30°C water bath and stirred for reaction. Then, 12.5 g of resorcinol was weighed and added to the solution and stirred for reaction for 10 min. (3) Then, add 27 ml of formaldehyde aqueous solution (37%-40%) to the solution in step (2) and stir to react for 5 minutes; (4) then adding anhydrous sodium carbonate in an amount 1 / 500 of the mass of resorcinol added to the solution in step (2) to the solution in step (3) and stirring the mixture for 30 minutes; (5) The mixed solution in step (4) was placed in a water bath with a temperature of 50°C and aged for 20 hours; (6) After the aged sample in step (5) is placed at room temperature for 1 hour, it is immersed in ethanol for 2 days, and the ethanol is replaced every day until all the water therein is replaced; (7) Dry the sample after replacement in step (6) at room temperature for 2 h, then place it in a constant temperature forced air drying oven and dry it at 85 °C for 12 h. After drying, take out the PF aerogel; (8) The PF aerogel in step (7) was transferred into a corundum boat, and then placed in a high-temperature tube furnace. After heating to 1000°C at 5°C / min in an argon atmosphere, the argon was turned off, and methane (CH4) and hydrogen (H2) were introduced at the same time, with a CH4 flow rate of 30ml / min and a H2 flow rate of 160ml / min. The temperature was kept constant at 1000°C for 8h. After the constant temperature was reached, the temperature was cooled at a rate of 10°C / min. When the temperature was cooled, the methane and hydrogen were turned off, and the argon was turned on. After the high-temperature tube furnace was cooled to room temperature, the argon was turned off, and the corundum boat was taken out to obtain the PF@VGSs carbon aerogel.
[0025] Example 3 (1) Add 60 ml of water and 40 ml of ethanol into a 250 ml beaker and stir for 30 seconds; (2) Then, the beaker containing the mixed solution in step (1) was moved into a 30°C water bath and stirred for reaction. Then, 22.5 g of resorcinol was weighed and added to the solution and stirred for reaction for 10 min. (3) Then, add 23 ml of formaldehyde aqueous solution (37%-40%) to the solution in step (2) and stir to react for 5 minutes; (4) then adding anhydrous sodium carbonate in an amount 1 / 2000 of the mass of resorcinol added to the solution in step (2) to the solution in step (3) and stirring the mixture for 30 minutes; (5) The temperature of the water bath heating device containing the mixed solution in step (4) was adjusted to 60°C and allowed to stand for aging for 12 hours; (6) After the aged sample in step (5) is placed at room temperature for 1 hour, it is immersed in ethanol for 4 days, and the ethanol is replaced once a day until all the water therein is replaced; (7) Dry the sample after replacement in step (6) at room temperature for 2 h, then place it in a constant temperature forced air drying oven and dry it at 85 °C for 12 h. After drying, take out the PF aerogel; (8) The PF aerogel in step (7) was transferred into a corundum boat, and then placed in a high-temperature tube furnace. After heating to 1300°C at 5°C / min in an argon atmosphere, the argon was turned off, and methane (CH4) and hydrogen (H2) were introduced at the same time, with a CH4 flow rate of 30ml / min and a H2 flow rate of 160ml / min. The temperature was kept constant at 1300°C for 6h. After the constant temperature was reached, the temperature was cooled at a rate of 10°C / min. When the temperature was cooled, the methane and hydrogen were turned off, and the argon was turned on. After the high-temperature tube furnace was cooled to room temperature, the argon was turned off, and the corundum boat was taken out to obtain the PF@VGSs carbon aerogel.
[0026] Example 4 (1) Add 60 ml of water and 40 ml of ethanol into a 250 ml beaker and stir for 30 seconds; (2) Then, the beaker containing the mixed solution in step (1) was moved into a 30°C water bath and stirred for reaction. Then, 20 g of resorcinol was weighed and added to the solution and stirred for reaction for 10 min. (3) Then, add 15 ml of formaldehyde aqueous solution (37%-40%) to the solution in step (2) and stir to react for 5 minutes; (4) then adding anhydrous sodium carbonate in an amount of 1 / 1500 of the mass of resorcinol added to the solution in step (2) to the solution in step (3) and stirring the mixture for 30 minutes; (5) The mixed solution in step (4) was placed in a water bath with a temperature of 30°C and aged for 36 hours; (6) After the aged sample in step (5) is placed at room temperature for 1 hour, it is immersed in ethanol for 3 days, and the ethanol is replaced every day until all the water therein is replaced; (7) Dry the sample after replacement in step (6) at room temperature for 2 h, then place it in a constant temperature forced air drying oven and dry it at 85 °C for 12 h. After drying, take out the PF aerogel; (8) The PF aerogel in step (7) was transferred into a corundum boat, and then placed in a high-temperature tube furnace. After heating to 1100°C at 5°C / min in an argon atmosphere, the argon gas was turned off, and methane (CH4) and hydrogen (H2) were introduced at the same time, with a CH4 flow rate of 30ml / min and a H2 flow rate of 160ml / min. The temperature was kept constant at 1100°C for 7h. After the constant temperature was reached, the temperature was cooled at a rate of 10°C / min. When the temperature was cooled, the methane and hydrogen gases were turned off, and the argon gas was turned on. After the high-temperature tube furnace was cooled to room temperature, the argon gas was turned off, and the corundum boat was taken out to obtain the PF@VGSs carbon aerogel.
[0027] Example 5 (1) Add 60 ml of water and 40 ml of ethanol into a 250 ml beaker and stir for 30 seconds; (2) Then, the beaker containing the mixed solution in step (1) was moved into a 30°C water bath and stirred for reaction. Then, 15 g of resorcinol was weighed and added to the solution and stirred for reaction for 10 min. (3) Then, add 24 ml of formaldehyde aqueous solution (37%-40%) to the solution in step (2) and stir to react for 5 minutes; (4) then adding anhydrous sodium carbonate in an amount 1 / 800 of the mass of resorcinol added to the solution in step (2) to the solution in step (3) and stirring the mixture for 30 minutes; (5) The mixed solution in step (4) was placed in a water bath at a temperature of 40°C and aged for 30 hours; (6) After the aged sample in step (5) is placed at room temperature for 1 hour, it is immersed in ethanol for 3 days, and the ethanol is replaced every day until all the water therein is replaced; (7) Dry the sample after replacement in step (6) at room temperature for 2 h, then place it in a constant temperature forced air drying oven and dry it at 85 °C for 12 h. After drying, take out the PF aerogel; (8) The PF aerogel in step (7) was transferred into a corundum boat, and then placed in a high-temperature tube furnace. After heating to 1200°C at 5°C / min in an argon atmosphere, the argon was turned off, and methane (CH4) and hydrogen (H2) were introduced at the same time, with a CH4 flow rate of 30ml / min and a H2 flow rate of 160ml / min. The temperature was kept constant at 1200°C for 6.5h. After the constant temperature was reached, the temperature was cooled at a rate of 10°C / min. When the temperature was cooled, the methane and hydrogen were turned off, and the argon was turned on. After the high-temperature tube furnace was cooled to room temperature, the argon was turned off, and the corundum boat was taken out to obtain the PF@VGSs carbon aerogel.
[0028] Example 6 (1) Add 60 ml of water and 40 ml of ethanol into a 250 ml beaker and stir for 30 seconds; (2) Then, the beaker containing the mixed solution in step (1) was moved into a 30°C water bath and stirred for reaction. Then, 18 g of resorcinol was weighed and added to the solution and stirred for reaction for 10 min. (3) Then, add 20 ml of formaldehyde aqueous solution (37%-40%) to the solution in step (2) and stir to react for 5 minutes; (4) then adding anhydrous sodium carbonate in an amount 1 / 1700 of the mass of resorcinol added to the solution in step (2) to the solution in step (3) and stirring the mixture for 30 minutes; (5) The mixed solution in step (4) was placed in a water bath at a temperature of 50°C and aged for 17 hours; (6) After the aged sample in step (5) is placed at room temperature for 1 hour, it is immersed in ethanol for 3.5 days, and the ethanol is replaced once a day until all the water therein is replaced; (7) Dry the sample after replacement in step (6) at room temperature for 2 h, then place it in a constant temperature forced air drying oven and dry it at 85 °C for 12 h. After drying, take out the PF aerogel; (8) The PF aerogel in step (7) was transferred into a corundum boat, and then placed in a high-temperature tube furnace. After the temperature was raised to 1250°C at 5°C / min in an argon atmosphere, the argon gas was turned off, and methane (CH4) and hydrogen (H2) were introduced at the same time, with a CH4 flow rate of 30ml / min and a H2 flow rate of 160ml / min. The temperature was kept constant at 1250°C for 6h. After the constant temperature was reached, the temperature was cooled at a rate of 10°C / min. When the temperature was cooled, the methane and hydrogen gases were turned off, and the argon gas was turned on. After the high-temperature tube furnace was cooled to room temperature, the argon gas was turned off, and the corundum boat was taken out to obtain the PF@VGSs carbon aerogel.
[0029] The three-dimensional graphene sheet array VGSs grown in situ on the PF aerogel in the present invention has better mechanical stability and higher specific surface area, and is grown in situ using the chemical CVD method, so that the VGSs will not agglomerate and will grow evenly inside and on the surface of the PF. The VGSs themselves can be independently self-supporting, so the composite material can form a three-dimensional porous structure with stronger mechanical stability and flexibility.
[0030] The carbon aerogel in the present invention is synthesized under the condition that the temperature is above 1000° C. during the entire CVD process, which can prove that the synthesized material has good high temperature resistance.
[0031] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0032] In addition, it should be understood that although this specification is described in accordance with the implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. The above content is only to illustrate the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution according to the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a carbon aerogel with high temperature resistance and high mechanical stability, characterized in that: The following steps are involved: After the ethanol solution containing resorcinol reacts with the formaldehyde solution, anhydrous sodium carbonate is added, and after the reaction, the solution is allowed to stand for aging to obtain a sample; The sample was soaked in ethanol and dried to obtain PF aerogel; A three-dimensional graphene sheet array was grown on PF aerogel using chemical CVD method to obtain a carbon aerogel with high temperature resistance and high mechanical stability.
2. The method for preparing high temperature resistant and mechanically stable carbon aerogel according to claim 1, characterized in that: The amount ratio of resorcinol, water and ethanol in the ethanol solution containing resorcinol is 12.5g~22.5g:60ml:40ml.
3. The method for preparing high temperature resistant and high mechanical stability carbon aerogel according to claim 1, characterized in that: The dosage ratio of resorcinol to formaldehyde solution is 12.5g~22.5g:15ml~27ml, and the mass concentration of formaldehyde solution is 37%~40%.
4. The method for preparing high temperature resistant and high mechanical stability carbon aerogel according to claim 1, characterized in that: The mass of anhydrous sodium carbonate is 1 / 500~1 / 2000 of the mass of resorcinol.
5. The method for preparing high temperature resistant and high mechanical stability carbon aerogel according to claim 1, characterized in that: The temperature for static aging is 30-60℃ and the time is 12-36h.
6. The method for preparing high temperature resistant and high mechanical stability carbon aerogel according to claim 1, characterized in that: The soaking time is 2-4 days.
7. The method for preparing high temperature resistant and high mechanical stability carbon aerogel according to claim 1, characterized in that: The VG array is grown on the PF aerogel by chemical CVD method to obtain a carbon aerogel with high temperature resistance and high mechanical stability, including the following steps: The PF aerogel was kept at 1000-1300°C for 6-8h under a mixed gas of methane and hydrogen.
8. The method for preparing high temperature resistant and high mechanical stability carbon aerogel according to claim 1, characterized in that: The temperature was raised to 1000-1300°C at a heating rate of 5°C / min under an argon atmosphere, kept at that temperature for 6-8h, and then cooled to room temperature at a cooling rate of 10°C / min under an argon atmosphere.
9. The method for preparing high temperature resistant and high mechanical stability carbon aerogel according to claim 1, characterized in that: The flow ratio of methane and hydrogen is 30:
160.
10. A carbon aerogel with high temperature resistance and high mechanical stability prepared according to the method of claim 1.
Citation Information
Patent Citations
Method for preparing graphene crosslinked type organic aerogel and carbon aerogel by normal-pressure drying
CN102774824A
Preparation method of high-specific-surface-area high-electric-conductivity graphene compound carbon aerogel based on chemical crosslinking
CN106365142A
High-strength large-size block carbon aerogel and preparation method and application thereof
CN107473199A
Graphene / boron nitride aerogel and preparation method thereof
CN114597560A
Carbon aerogel-pyrolytic carbon composite material and preparation method thereof
CN117342540A